HYPERTENSIVE DISEASE AS A PRIMARY RISK FACTOR FOR STROKE - Pulatova Sh. B.; Musaeva Yu. A.; Tavmuradova M. G. (Web of Journals Publishing, 2025)
This article focuses on hypertensive disease as a primary risk factor for stroke, contributing to mortality and disability in the population. It describes the mechanisms by which elevated blood pressure affects the vascular system and the impact of this condition on stroke status. Current statistical data are discussed, as well as methods for monitoring and managing hypertension for prevention and counseling.
Keywords: Hypertensive disease, stroke, arterial hypertension.